2020
DOI: 10.3390/biom10121700
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations Predict that rSNP Located in the HNF-1α Gene Promotor Region Linked with MODY3 and Hepatocellular Carcinoma Promotes Stronger Binding of the HNF-4α Transcription Factor

Abstract: Our study aims to investigate the impact of the Maturity-onset diabetes of the young 3 disease-linked rSNP rs35126805 located in the HNF-1α gene promotor on the binding of the transcription factor HNF-4α and consequently on the regulation of HNF-1α gene expression. Our focus is to calculate the change in the binding affinity of the transcription factor HNF-4α to the DNA, caused by the regulatory single nucleotide polymorphism (rSNP) through molecular dynamics simulations and thermodynamic analysis of acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…One study suggests that up to 29% of HNF4A-MODY cases may be incorrectly credited to HNF1A-MODY and sequencing of HNF4A is proposed when there is no mutation in HNF1A [ 127 ]. Recently, it was shown that single nucleotide polymorphism located in the HNF1A gene promoter can affect the binding of HNF4A and subsequently regulate HNF1A gene expression [ 128 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…One study suggests that up to 29% of HNF4A-MODY cases may be incorrectly credited to HNF1A-MODY and sequencing of HNF4A is proposed when there is no mutation in HNF1A [ 127 ]. Recently, it was shown that single nucleotide polymorphism located in the HNF1A gene promoter can affect the binding of HNF4A and subsequently regulate HNF1A gene expression [ 128 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…Monogenic diabetes, a rare form of diabetes seen in young people (types 4 and 5), is associated with heterozygous mutations in some genes, such as PDX1 and HNF1A. Variants of PDX1 and HNF1A genes are also linked with an increased risk of obesity, T2DM, or hyperglycemia [60][61][62]. Figure 2 summarizes the different mechanisms that are involved between T2DM and the development of PC [28].…”
Section: Genetic Mutations Driving Pancreatic Cancermentioning
confidence: 99%
“…Heterozygous mutations in some of these genes, such as PDX1 and HNF1A, also lead to different types of monogenic diabetes in young people (types 4 and 5). Some variants in PDX1 and HNF1A are also associated with an increased risk of T2DM (64,65), obesity, or hyperglycemia (66).…”
Section: Genetics Factors Driving Dm and Pcmentioning
confidence: 99%